Fitur Live Streaming Sebagai Strategi Digital Marketing - Wiranda, Aditya; Hayu, Rina Suthia (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
Live streaming commerce is defined as a part of e-commerce that is equipped with real-time social interactions, a unique feature for conducting live broadcasts. This research aims to create a marketing strategy using the live streaming feature on Indonesian social media and e-commerce. This research uses literature review and phenomenon observation methods. The research results produced a marketing strategy using the live streaming feature consisting of 5 approaches and 14 strategies.